Single crystals of insoluble porous salicylimine cages - Holsten, Mattes; Elbert, Sven; Rominger, Frank; Zhang, Wen-Shan; Schröder, Rasmus R.; Mastalerz, Michael (Chemistry - a European journal, 2023)
Porous organic cages (POCs) are meanwhile an established class of porous materials. Most of them are soluble to a certain extend and thus processable in or from solution. However, a few of larger salicylimine cages were reported to be insoluble in any organic solvents and thus characterized as amorphous materials. These cages were now synthesized as single-crystalline materials to get insight into packing motifs and preferred intermolecular interactions. Furthermore, the pairs of crystalline and amorphous materials for each cage allowed to compare their gas-sorption properties in both morphological states.